Paths to Transdisciplinarity: Reconnecting Pathways and Positionality - Lawrence, Roderick J. (World futures, 2025)
Transdisciplinarity is evolving with multiple pathways. I consider paths serve as metaphors for making choices, for pursuing a goal, for confronting obstacles or taking the easy way out. All literal and metaphorical paths are human made. Path metaphors help us better understand multiple definitions and interpretations of transdisciplinarity that coexist and do not necessarily converge. I posit that a trans-anthropo-logic can accommodate divergent paths because it incorporates the positionality of individuals and groups in society and their situatedness about specific subjects. Path metaphors enable reflexive thinking and dialogue between people on different paths about global understandings of complex societal challenges. Transdisciplinarity is evolving with multiple pathways that coexist. Path metaphors help understand multiple interpretations of transdisciplinarity. Path metaphors enable reflexive thinking and dialogue between people on different paths. Researchers and practitioners should consciously position themselves on paths.